BEYOND TRADITIONAL RISK FACTORS : A REVIEW OF ENVIRONMENTAL EXPOSURES IN CARDIOVASCULAR DISEASE - Tjahjono, Cholid Tri; Arthamin, Maimun Zulhaidah; Prakosa, Ardani Galih; Insanitaqwa, Aleyda Zahratunany (Universitas Brawijaya, 2025)
Traditional cardiovascular disease (CVD) risk models frequently overlook environmental factors, despite increasing evidence that exposures such as air pollution, toxic chemicals, noise, and extreme temperatures markedly elevate CVD risk via common biological mechanisms. This review integrates contemporary evidence regarding the impact of environmental exposures on cardiovascular risk, exploring mechanistic insights, preventive strategies, and prospective research opportunities within the fields of environmental cardiology. We performed a narrative review of recent studies to assess environmental factors influencing cardiovascular health. Environmental exposures increases cardiovascular risk through oxidative stress, inflammation, autonomic imbalance, and endothelial dysfunction. Fine particulate matter (PM2.5), ozone, heavy metals, PFAS, noise pollution, and extreme temperatures are consistently linked to hypertension, arrhythmias, myocardial infarction, and stroke. People who work outside and older adults are more at risk than others. Urban redesign, monitoring of exposure, protective workplace interventions, and regulatory policies are all examples of preventive strategies. The exposome provides an effective framework for comprehensive exposure assessment. There are still big gaps in research, especially in low- and middle-income countries. This review underscore the imperative to underscore environmental risk factors in the prevention of CVD. Combining long-term research, data-driven policies, and personalized strategies is necessary to reduce the global burden of CVD and promote health equity.